Importance of Multidrug Efflux Pumps in the Antimicrobial Resistance Property of Clinical Multidrug-Resistant Isolates of Neisseria gonorrhoeae - Golparian, Daniel; Shafer, William M.; Ohnishi, Makoto; Unemo, Magnus (Antimicrobial agents and chemotherapy, 2014)
The contribution of drug efflux pumps in clinical isolates of Neisseria gonorrhoeae that express extensively drug-resistant or multidrug-resistant phenotypes has heretofore not been examined. Accordingly, we assessed the effect on antimicrobial resistance of loss of the three gonococcal efflux pumps associated with a known capacity to export antimicrobials (MtrC-MtrD-MtrE, MacA-MacB, and NorM) in such clinical isolates. We report that the MIC of several antimicrobials, including seven previously and currently recommended for treatment was significantly impacted.